Carotid distension waves acquired with a fiber sensor as an alternative to tonometry for central arterial systolic pressure assessment in young subjects. (January 2017) - Leitão, C.; Antunes, P.; Pinto, J.L.; Bastos, J.M.; André, P.
Abstract: In this work it is evaluated the possibility of central blood pressure assessment using distension waves, obtained with a low cost optical fiber sensor, instead of regular arterial tonometry. Carotid distension and pressure waveforms were acquired in 15 young subjects. Form factors, root-mean-square error (RMSE), harmonic decomposition and central systolic pressures for both techniques were analysed. The pressure waves assessed by the piezoelectric probe had lower form factors than the ones assessed by the optical fiber sensor, due to the different nature of the waves (51.05 ± 5.15% versus 40.53 ± 5.70%), translating in a RMSE of 14 ± 2%. Regarding the harmonic analysis, paired t -tests shown that the first four harmonics are not significant different (p ⩽ 0.05), and Pearson correlation studies retrieve that the 2nd–7th harmonics are correlated (p ⩽ 0.03). Central systolic pressures were also obtained with both techniques displaying a very strong Pearson correlation (0.99) and a small difference of 0.63 ± 2.40 mmHg. These pre-clinical results support a future clinical validation study in larger and broader cohorts.